Basic Education in Cambodia: The Impact of UNESCO onPolicies in the 1990s - Dy, Sideth S.; Ninomiya, Akira (Education Policy Analysis Archives, 2003)
Efforts to enhance opportunities for Basic Education have been growing within many developing nations after the1990 World Conference on Education For All (WCEFA) in Jomtien, Thailand. In the face of political turmoil, financial constraint and social insecurity, Cambodia with the encouragement and assistance of the United Nations Educational, Scientific, and Cultural Organization (UNESCO), took measures to increase educational opportunities for all her citizens through Basic Education strategic plans and pledged to eradicate illiteracy by the year 2000. This article examines the joint efforts during the 1990s of this organization as a key assistance and support UN agency for educational policy and strategy formulations, and the Cambodian government as a national agency for educational initiatives and implementation. UNESCO’s inputs for policy implementation are also detailed to evaluate the overall impact of the organization during the last decade. Analyses are based primarily on interviews with some key government policymakers, fieldwork observation and interviews with school-aged children, several speeches of top government officials, and existing related official education statistics and indicators in Cambodia.